Human Papillomavirus-Negative Cervical Cancer: A Comprehensive Review - Xing, Biyuan; Guo, Jianfeng; Sheng, Yuhan; Wu, Gang; Zhao, Yingchao (Frontiers in Oncology, 2021)
Human papillomavirus (HPV) has been known to be the leading cause of cervical cancer for more than 25 years. Approximately 5.5%–11% of all cervical cancers are still reported to be HPV-negative, which could be attributed to misclassification of histology, truly negative cases, and false-negative cases. The truly HPV-negative cervical cancers are almost cervical adenocarcinomas with unclear etiology. The false-negative cases include latent infections of HPV, disruption of targeting fragment, non-high-risk HPV infection, and false-negative HPV testing. HPV-negative cervical cancers have advanced FIGO stage and poor prognosis, thereby requiring more attention towards the management of these cases.